THE RELEVANCE OF VERBAL PREFIX FORMATIONSIN DAF LESSONS - Abdreymova, D.A. (SCIENCE and SOCIETY, 2023)
In this article, prefixed verbs are considered from different points of view, and the use of prefixes with verbs at the end of sentences can be used as an example of the complex structure of the German language.